Assessment of Phosphorus Sorption and Desorption Characteristics of Tropical Acid Soil Applied with Paddy Husk Compost - Umi Zahrah Nanyan (2019)
Phosphorus (P) is an essential component of adenosine triphosphate (ATP), which is involved in most biochemical processes in plants and enables them to extract nutrients from the soil. It plays an important role for root growth, it is often major element in starter fertilizers, those applied at planting. Applications of organic amendment is highly recommended in reduce phosphorus sorption and improve the Phosphorus availability in the soil. Thus, the objective of this study are to determine the changes in the soil P sorption and desorption upon application of paddy husk compost and the soil maximum P buffering capacity of the soil upon applied of paddy husk compost. Paddy husk compost was used and the sorption data were fitted to the Langmuir Equation. The results proved that at initial P concentration of < 20 mg L-1, sorbed P increased with the amendment of paddy husk compost while more Phosphorus desorbed with increasing P application rates (20 to 30 mg L-1). The decreases in P sorption in this study was due to the precipitation of exchangeable aluminium and iron at the highly negatively charged humic substances functional group surfaces of the organic amendment. The sorption of phosphorus was enhanced by increase of soil pH due to application of organic amendments. Besides, amending of paddy husk compost showed high buffering capacity and increased the availability of phosphorus in acid soil used in this study. The finding shows suggests that the application of paddy husk compost can enhanced the soil phosphorus availability by changing the soil sorption and desorption capacity and pH buffering capacity.